The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1038/bjc.1989.16
|View full text |Cite
|
Sign up to set email alerts
|

The dedifferentiation of metastatic prostate carcinoma

Abstract: Summary Two hundred consecutive staging lymphadenectomies with metastatic prostate adenocarcinoma and 100 consecutive autopsies with widely disseminated metastatic prostate adenocarcinoma were identified. The metastases from 41% of the staging lymphadenectomies were entirely differentiated (gland forming) and an additional 43% were predominantly (50% or more) differentiated. In contrast, the metastases from 70% of the autopsies were entirely undifferentiated (non-gland forming) and an additional 18% were predo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…Autopsy studies suggest that a subset of patients with prostate cancer die from pure AR- negative NEPC(2021) but this incidence may be under-recognized. Patients are not typically biopsied late in the stages of PCA to evaluate for NEPC progression, but can be suspected in patients with progressive disease despite a normal or modestly elevated PSA and elevated serum markers of neuroendocrine differentiation (i.e., chromogranin A or NSE)(1).…”
Section: Discussionmentioning
confidence: 99%
“…Autopsy studies suggest that a subset of patients with prostate cancer die from pure AR- negative NEPC(2021) but this incidence may be under-recognized. Patients are not typically biopsied late in the stages of PCA to evaluate for NEPC progression, but can be suspected in patients with progressive disease despite a normal or modestly elevated PSA and elevated serum markers of neuroendocrine differentiation (i.e., chromogranin A or NSE)(1).…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Several authors studied dedifferentiation by comparing differentiation in metastases and primary tumors 20,21 and concluded that there is a trend toward histological dedifferentiation when prostate carcinoma metastasizes to regional lymph nodes. It could be argued however, that these observations are the consequence of a higher potential for metastasis of poorly differentiated tumor cells, rather than dedifferentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the great difficulties involved in the assessment of response criteria in advanced prostatic cancer, the use of bone and prostatic tumour markers, together with other evaluation criteria such as performance status, bone pain and a, (Hetherington et al, 1988;Speights, 1989;Jacobs et al, 1980Jacobs et al, ): al., 1991Francini et al, 1992).…”
Section: Discussionmentioning
confidence: 99%